Differences in cortico‐striatal‐cerebellar activation during working memory in syndromal and nonsyndromal children with prenatal alcohol exposure. Issue 8 (25th March 2012) - Diwadkar, Vaibhav A.; Meintjes, Ernesta M.; Goradia, Dhruman; Dodge, Neil C.; Warton, Christopher; Molteno, Christopher D.; Jacobson, Sandra W.; Jacobson, Joseph L.
Abstract Although children with heavy prenatal alcohol exposure may exhibit the distinctive facial dysmorphology seen in full or partial fetal alcohol syndrome (FAS/PFAS), many lack that dysmorphology. This study examined the functional organization of working memory in the brain in three groups of children—those meeting diagnostic criteria for FAS or PFAS, heavily exposed (HE) nonsyndromal children, and healthy controls. A verbal n‐back task (1‐back and 0‐back) was administered to 47 children (17 with FAS/PFAS, 13 HE, and 17 controls) during fMRI. Intra‐group one‐sample t‐tests were used to identify activity regions of interest central to verbal working memory including the dorsal prefrontal cortex (dPFC), inferior frontal gyrus, caudate/putamen, parietal cortex, and cerebellar Crus I/lobule VI and lobule VIIB‐IX. Whereas groups did not differ in task sensitivity, fMRI analyses suggested different patterns of sub‐network recruitment across groups. Controls primarily recruited left inferior frontal gyrus (Broca's area). By contrast, HE primarily recruited an extensive set of fronto‐striatal regions, including left dPFC and left caudate, and the FAS/PFAS group relied primarily on two cerebellar subregions and parietal cortex. This study is, to our knowledge, the first to demonstrate differential recruitment of critical brain regions that subserve basic function in children with different fetal alcohol spectrum disorders compared to controls. The distinct activation patterns seen in the two exposed groups may be related to substantial differences in alcohol dose/occasion to which these groups were exposed in utero. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.